News sharing as a measure of media alignment - Gábor Simonovits; Ádám Vig (Journal of Quantitative Description: Digital Media)
In this note we introduce a new approach to measure media alignment derived from the story-sharing behavior of journalists. We use a large corpus of online news stories from two leading Hungarian news sites and estimate alignment scores for a large number of outlets that they cite. To the extent that journalists are more likely to cite ideologically proximate sources, our measure can be used to compare a large number of media outlets on a political — in our case government vs. independent — space. We demonstrate the use of this approach with two empirical applications. First, we show that our alignment scores successfully capture known ideological variation across outlets at a single point in time. Second, we demonstrate that quarterly estimates of alignment for a captured outlet change dramatically following an abrupt change in ownership.